Skrining obesitas dan pemeriksaan kadar glukosa darah pada masyarakat di Posyandu Lansia Raflesia Kelurahan 20 Ilir Palembang - Rasyid, Riana Sari Puspita; Susilawati, Susilawati; Diba, Masayu Farah; Syifa, Syifa; Hasbi, Alfian; Hidayatullah, Mohammad Wahyu; Syahranni, Dhanya (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Obesity is an excessive accumulation of fat due to an imbalance in energy intake (eating, drinking) with the energy used for a long time. Obesity is a modifiable risk of diabetes mellitus (DM). Screening for obesity and blood glucose in at-risk individuals is very important to prevent the incidence of DM. Routine nutritional status and blood glucose examinations for susceptible ages and people with DM still need to be carried out to monitor therapy and prevent severity. One way that can be used to determine obesity is through an abdominal circumference examination. The normal abdominal circumference for women is 80 cm for and for men 90 cm. This community service activity is aimed at the early detection of obesity and DM incidence by targeting the elderly and elderly in the 20 Ilir D-IV Village. The activity was carried out by lecturers and students of the Faculty of Medicine, Sriwijaya University, in collaboration with cadres of the Raflesia Elderly Posyandu, Kelurahan 20 Ilir D-IV, in the working area of ​​the Talang Ratu Health Center. The results of the examination showed that most of the participants were centrally obese, but only 2 people had blood glucose levels >200 mg/dL. It is necessary to periodically screen through the Raflesia Elderly Posyandu and creates a program to reduce the level of central obesity and increase blood glucose levels in the community of Kelurahan 20 Ilir D-IV.